Examining Portuguese High School Students’ Attitudes Toward Physical Education - Pereira, Paulo; Santos, Fernando; Marinho, Daniel A. (Frontiers in Psychology, 2020)
Portugal ranks fourth among countries with the highest rate of overweight population, considering that 67.6% of the Portuguese population over the age of 15 is overweight or obese. To our knowledge, there are limited studies that have investigated students’ attitudes toward physical education in the Portuguese context. Such research is necessary because it can provide valuable insights for policy and application in the curriculum development for physical education which may eventually increase participation in physical and sports activities. This study analyzed students’ attitudes toward physical education (PE) according to sociodemographic variables such as grade level, socioeconomic status, and gender, as well as participation in extracurricular sports activities and respective grades obtained in PE. The sample was composed of 476 high school students (from the 7th, 8th, and 9th grade levels) from five public schools located in Portugal. The Students’ Attitudes toward Physical Education questionnaire was adapted and validated to be used with Portuguese students as a two-factor model was created. Findings show that students generally have a moderately positive attitude toward physical education. However, students’ positive attitudes tend to decrease throughout high school, which is particularly significant in the 9th grade. Further, students’ attitudes are influenced by gender, extracurricular sports practice, and grades. These findings may help stakeholders reflect on how to better frame physical education in a meaningful way that will create a solid foundation toward maintaining an active lifestyle throughout life. Implications for further research and practice are discussed.